Before Utopia: the making of Thomas More's mind - Dealy, Ross (University of Toronto Press, 2020)
Introduction: In search of the meaning of Utopia -- The mystery of More's "Either/or" 1505 decision: bodily and mental issues before late 1504 -- More's radically new, both/and, paradigm: Erasmus' De taedio Iesu and the Enchiridion, 1503 -- More's Lucian, 1506, and Utopia: teaching Stoic two-dimensional Christianity -- Thomas More as unitarily "democritus" and "the man for all seasons": Erasmus' preface to The praise of folly, 1510 -- A Stoic/Morean Praise of folly, 1511: The praise of folly works out More's Stoic-framed transformation -- Utopian philosophy, 1516: Epicureanism within a Stoic Honestum/Utile frame -- Utopian warfare: a unitary two-dimensional mindset -- What Wiseman Hythloday did not understand.